Qualidade da carne de cordeiros Santa Inês alimentados com resíduo de cervejaria desidratado - Feitosa, Mara Sampaio (2017)
This study aimed to evaluate the meat quality of Santa Ines lambs fed with brewers dried grains (BDG). Thirty-five male non-castrated animals, with mean initial body weight of 16.00 ± 1.69 kg and approximately 70 days of age, were used. A completely randomized design was used, with five experimental rations and seven replicates, the rations consisting of 0; 20; 40; 60 and 80% inclusion of BDG in the concentrated portion of the feed. The duration of the experiment was determined by the time required for the mean body weight of the animals in one of the treatments to reach 28 kg at which time the 35 animals were slaughtered. The Longissimus lumborum and Semimembranosus muscles were used for analyzes of centesimal composition, shear force, color, pH, weight loss per cooking and water retention capacity. The percentages of inclusion of the BDG in the experimental rations influenced (P <0.05) the variables of the centesimal composition of the evaluated muscles, except for the moisture and mineral matter contents in the Semimembranosus muscle. For the physicochemical characteristics of the Longissimus lumborum muscle, there was effect of the rations (P<0.05) on the color parameters (L*, a*, b*, H) were observed, where the luminosity (L*) and intensity of yellow color (b*) presented a quadratic behavior, the intensity of red color (a*) increasing linear behavior, while for the color tone (H*) a linear behavior was observed, decreasing with the inclusion of BDG in the rations. As the amount of residue in the feed of the animals was increased, there was an increase of the shear force applied in the muscle and a reduction of the pH. For the Semimembranosus muscle, the inclusion of the by-product in the experimental rations influenced (P<0.05) the variable weight loss by cooking, showing an increasing linear behavior, and a linear decreasing behavior was observed for the pH. In relation to the lipid, cholesterol and fatty acid content found in the Longissimus dorsi muscle, it was observed that the rations containing the brewery residue did not influence the lipid content (P>0.05). However, they did have a quadratic effect (P<0.05) in cholesterol levels. Oleic (C18:1 n-9), palmitic (C16:0) and stearic (C18:0) fatty acids were found in higher concentrations in the muscle analyzed. There was a decreasing linear behavior (P<0.05) for linolenic fatty acid (C18:3n-3) and the highest percentages of linoleic acid (C18:2) were observed in rations that did not contain RCD. The desirable fatty acids and the n-6 / n-3 relation presented a linear decreasing effect (P<0.05), while the thrombogenicity index increased linearly (P<0.05) with the inclusion of BDG (P<0.05). Quadratic effect was observed for the polyunsaturated fatty acids (PUFA), for the polyunsaturated: monounsaturated (AGPI:AGMI) and (C18: 0 + C18:1)/(C16:0), for the atherogenicity index (AI) and for the ratio between hypocholesterolemic and hypercholesterolemic fatty acids (h/H). The inclusion of dehydrated brewery residue increases protein deposition and reduces the percentage of lipids, attributes desired by the consumer. The meat of lambs fed BDG, at increasing levels, presents reduction in softness, elevation in saturated fatty acids contents and reduction in the profile of desirable fatty acids. In this way, the addition of BDG in up to 20% of the concentrated portion may be recommended depending on the viability of acquisition.